Acid Dissociation Constants, Enthalpy, Entropy and Gibbs Energy of Bedaquiline by UV-Metric Spectral and pH-metric Analysis - Meloun, Milan; Cyrmonová, Daniela; Javůrek, Milan; Pekárek, Tomáš (My University, 2021)
Bedaquiline (trade name Sirturo) is an antibiotic used to treat pulmonary tuberculosis that is resistant to other antibiotics. The pH-spectrophotometric and pH-potentiometric titration allowed the measurement of two near successive and one distant dissociation constants. Bedaquiline neutral LH molecule was able to protonate and dissociate in pure water to form soluble particles L-, LH, LH2+, LH32+ and LH43+. In the pH range 2 to 7, three dissociation constants can be reliably estimated. REACTLAB (UV-metric spectral analysis): pKTa1 = 3.91(09), pKTa2 = 4.58(12) and pKTa3 = 5.26(07) at 25 °C and pKTa1 = 3.61(30), pKTa2 = 4.44(15) and pKTa3 = 5.54(33) at 37 °C. ESAB (pH-metric analysis): pKTa1 = 3.21(39), pKTa2 = 3.68(31) and pKTa3 = 5.21(42) at 25 °C and pKTa1 = 3.31(12), pKTa2 = 3.67(15) and pKTa3 = 5.73(08) at 37 °C. Molar enthalpy ΔH0, molar entropy ΔS0 and Gibbs free energy ΔG0 were calculated from the spectra using a dependence ln K to 1/T. The potentiometric data showed positive enthalpy ΔH0(pKa1) = 85.49 kJ·mol-1, ΔH0(pKa2) = 86.42 kJ·mol-1, ΔH0(pKa3) = 65.84 kJ·mol-1 and dissociation was endothermic. The entropy ΔS0 at 25 ° C was positive for 3 dissociation constants ΔS0(pKa1) = 217.47 J·mol-1, ΔS0(pKa2) = 204.87 J·mol-1, ΔS0(pKa3) = 92.63 J·mol-1 at 25 °C and proved irreversible dissociation.
Kyselé disociační konstanty, entalpie, entropie a Gibbsova energie Bedaquilinu analýzou UV-spekter a pH-měření.
Keywords: dissociation constants; Bedaquiline; spectrophotometric titration; pH-titration; REACTLAB; SQUAD84; ESAB; disociační konstanty; Bedaquiline; spektrofotometrická titrace; pH-titrace; REACTLAB; SQUAD84; ESAB